Herausbildung erster Wesenszüge des Normalarbeitsverhältnisses in Deutschland - Michael J. Kendzia (Institute for the Study of Labor (IZA), 2010)
The paper provides a historical overview of the development of the initial characteristics of the standard employment contract in Germany from the middle of the 19th century until the beginning of World War I. The beginning of the welfare state in Germany took place during the 1880s on the basis of dependent employment. For the analysis of this type of employment, the model of the standard employment contract is used, and the specific factors which determined the rise of the standard employment contract are examined. In the 19th century, wage labour became more and more common and finally displaced the pre-modern allocation of work. After being freed from feudal dependence, the familiar social question arose. In this context, the main driving forces as well as different approaches in solving this question are surveyed. State regulations were implemented to protect the workforce against exploitation by industrial entrepreneurs. Later on, a social insurance system was created to protect workers against basic risks. The paper finds that prior to the establishment of the social insurance system, a number of insurance funds had existed which were financed by worker contributions. Moreover, these insurance funds already contained the essential structural elements of the later Bismarckian welfare system. The paper concludes that at the end of the observed period, dependent, full-time employment subject to social insurance contributions can be identified.
Keywords: J50; J40; 330; Abhängiges Beschäftigungssystem; Normalarbeitsverhältnis; Soziale Frage; Soziale Sicherung; Bismarck; Sozialversicherungsgesetzgebung